(untitled) (Libya Journal of Geographical Studies, 2023)
This study aimed to find out the change in the size and growth of the population and the extent of its impact on the geographical distribution of the population in the city of Ajdabiya for the period (1973-2020), follow up the changes that occurred in the population mass in the city, and interpret these changes using geographic information systems technology, in addition to using some statistical methods to track the change. In the city, including the Hoover index to measure population concentration, the Lorenz curve, and the Gini index to measure population disparity and the rate of population density between the city’s shops. On (71.6%) of the area of the city and that there is a kind of balance between the population and the area in which they live, and the shape of the population distribution appears in a state close to ideal and evenly over the entire area unit of the city, and this was evidenced by the Gini index, which had a value of (0.1) in 2022 AD The study recommended the need to apply planning standards to contain the areas located outside the plan and provide them with the facilities and services that the population needs.